GOVERNMENT EXPENDITURES ON EDUCATION, RESEARCH AND DEVELOPMENT (R&D) AND THEIR IMPACTS ON THE INDONESIAN ECONOMY - Muhammad Nasir (Jurnal Pencerahan, 2014)
This paper is aimed at descriptively discussing the impact of government expenditures on education, Research and Development (RD) on the national economy of Indonesia. In the analysis, the method used in this research is library research with an in-depth analysis and discussion on many related policies that effect technological change and economic growth in Indonesia. The findings show that Indonesian government has introduced a number of supporting policies related to education as well as RD to promote economic growth of the country. These policies generally have started since New Order government in the late 1960s. However, New Order government has put the strong bases to encourage trade openness and investment especially foreign investment. On the meantime, the government had also involved in free trade cooperation such as Asia Pacific Economic Cooperation (APEC) which will be applied 2020 for the developing countries and 2010 for the developed countries. Even the government has generated numbers of favourable policies to attract foreign investment and fastening economic growth, the policies in generating public RD has been not well developed. The government budget spends for public RD is still low (around 2 percent every year). Based on the research findings, it is recommended for the government to increase the spending on education and RD in order to increase economic growth